THE ABUNDANCES OF SOME HEAVY ELEMENTS IN THE ATMOSPHERE OF γ TAURI - Yushchenko, A. V.; Gopka, V. F. (Одеські астрономічні публікації, 2017)
Comparison of synthetic spectrum of the γ Tauri photosphere and high quality spectral atlases of this star permit us to identify absorption lines of rubidium, indium, disprosium, erbium, osmium in the observed spectra. The abundances of these elements in the atmosphere of γ Tauri with respect to their abundances in the solar atmosphere were determined by the method of spectrum synthesis.